Consideration of comorbidity in risk stratification prior to prostate biopsy. Issue 13 (25th April 2013) - Liss, Michael A.; Billimek, John; Osann, Kathryn; Cho, Jane; Moskowitz, Ross; Kaplan, Adam; Szabo, Richard J.; Kaplan, Sherrie H.; Greenfield, Sheldon; Dash, Atreya
<x xml:space="preserve">Abstract</x> BACKGROUND Previously, the patient‐reported Total Illness Burden Index for Prostate Cancer (TIBI‐CaP) questionnaire and/or the physician‐reported Charlson Comorbidity Index (CCI) have provided assessments of competing comorbidity during treatment decisions for patients with prostate cancer. In the current study, the authors used these assessments to determine comorbidity and prognosis before prostate biopsy and the subsequent diagnosis of prostate cancer to identify those patients least likely to benefit from treatment. METHODS A prospective observational cohort study was performed of 104 participants aged 64.0 years ± 6.5 years from 3 institutions representing different health care delivery systems. Patients were identified before undergoing transrectal ultrasound‐guided prostate biopsy and followed for a median of 28 months. Associations between the comorbidity scores and nonelective hospital admissions were investigated using logistic regression and Cox proportional hazards models. RESULTS Among the 104 patients who underwent prostate biopsy, 2 died during the follow‐up period. The overall hospital admission rate was 20% (21 of 104 patients). Higher scores on both the TIBI‐CaP (≥ 9) and CCI (≥ 3) were found to be significantly associated with an increased odds for hospital admission (odds ratio, 11.3 [95% confidence interval (95% CI), 2.4‐53.6] and OR, 5.7 [95% CI, 1.4‐22.4]) and hazards ratios (HRs) for time to hospital admission (HR, 3.8 [95% CI, 1.3‐11.2] and HR, 3.2 [95% CI, 1.1‐9.1]), respectively. CONCLUSIONS TIBI‐CaP and CCI scores were found to successfully predict which patients were at high risk for nonelective hospital admission. These patients are likely to have poorer health and a potentially shortened lifespan. Therefore, comorbidity analysis using these tools may help to identify those patients who are least likely to benefit from prostate cancer therapy and should avoid prostate biopsy. Cancer 2013;119:2413‐2418. © 2013 American Cancer Society.